A comparative analysis of bioeconomy visions and pathways based on stakeholder dialogues in Colombia, Rwanda, Sweden, and Thailand. Issue 6 (2nd November 2022) - Johnson, Francis Xavier; Canales, Nella; Fielding, Matthew; Gladkykh, Ganna; Aung, May Thazin; Bailis, Rob; Ogeya, Mbeo; Olsson, Olle
ABSTRACT: The bioeconomy offers a cross-cutting perspective on the societal transformation towards long-term sustainability and the transition away from the non-renewable economy. Identification of future pathways towards a sustainable bioeconomy can be related to different 'visions' of the bioeconomy, including an ecological vision, a bioresource development vision and a biotechnology vision. This paper synthesises empirical work from stakeholder dialogues conducted in Colombia, Rwanda, Sweden, and Thailand. The dialogues were structured around elaboration of bioeconomy pathways arising from different visions. The dialogues considered key driving factors and enabling conditions for different institutional levels ranging from local to regional. By conducting analysis across multiple countries and regions, we aimed to look across different economic development levels, different sectoral perspectives, and different innovation and bioresource strategies. Key components for bioeconomy pathways were identified with respect to bio-based products and resources, sectoral alignment, innovation clusters or hubs, and landscape transitions. The choice of different bioeconomy pathways is characterised by tensions between sector-based development and cross-cutting approaches, which in turn reflect differences between the bioresource and ecological visions, whereas the biotechnology vision tends to be viewed more as a means of implementation. The comparative analysis suggests some future lines of research on governing bioeconomy pathways.